Proceedings of the Conference on Undergraduate Preparation for Professional Education in Speech Pathology and Audiology (New Orleans, Louisiana, February 24-26, 1969) - American Speech and Hearing Association, Washington, DC.; Ashmore, Lear; Hanson, Grace; American Speech and Hearing Association, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
The description of the conference of the American Speech and Hearing Association is introduced by a discussion of the background and procedures used in the conference. The general areas dealt with in the discussions were the necessary skills and knowledge of speech pathologists and audiologists, the improvement of professional education curricula, and methods of determining professional competency. Group discussions summarized cover education at the B.A. level, more flexible undergraduate programs, programs to develop various skills to be used in a multidisciplinary approach, a delineation of the basic knowledges needed, programs for paraprofessionals, the functions of the clinical practitioner, and standards of necessary experience and degree levels. Evaluation questionnaires on the structure and content of the conference, a list of participants, and a list of distributed materials are included. (JM)
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
Sponsoring Agency: Rehabilitation Services Administration (DHEW), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Allied Health Personnel; College Curriculum; College Programs; Communication Problems; Curriculum Development; Hearing Impairments; Personnel Evaluation; Professional Occupations; Professional Training; Speech Handicaps; Speech Therapy; Standards; Therapists; Audiology; Conference Reports; Professional Education; Speech Pathology; Undergraduate Study